Accuracy, time cost and terrain independence comparisons of levelling techniques - El-Ashmawy, Khalid L. A. (Geodesy and Cartography, 2014)
Levelling techniques is classified as geometric levelling, trigonometric levelling and GPS/Levelling depending on used instruments or the methods applied. Accuracies of geometric levelling with using three equipments (Leica NA-720 optical level, Topcon RL-VH4G2 laser level and Leica NA-3003 digital level), the trigonometric levelling with using two equipments (Topcon GTS710 total station and Topcon Imaging Station) and GPS/levelling with using Sokkia GSR2600 receiver were investigated to determine their performances against precise levelling that yields the most precise results. For this purpose, measurements were taken at hundred points on the ground of a well-protected site. The comparison of the results was performed based on accuracy, time cost and terrain independence. The comparison shows that levelling using digital level produces the closets results to precise levelling results, the time cost of GPS/levelling was 74% and 41% less than geometric and trigonometric levelling respectively, and trigonometric and GPS/levelling are independent of the terrain surveyed.